Safety and pharmacokinetics of the muscarinic positive allosteric modulator VU319: A phase 1 single dose study: Human/Human trials: Cognitive enhancement. (7th December 2020) - Newhouse, Paul A.; Conley, Alexander C.; Key, Alexandra P.; Blackford, Jennifer U.; Rook, Jerri M.; Conn, Jeffrey; Lindsley, Craig W.; Jones, Carrie K.
Abstract: Background: The investigational new drug VU319 has recently completed first‐in‐human testing in a Phase 1 Single Ascending Dose (SAD) study, which included a Food Effect substudy. The main objectives of the SAD study were to assess the safety and tolerability of VU319 in healthy adults. The Food Effect substudy examined whether the metabolism and absorption of VU319 changed when administered in a fed compared to a fasted state. Both studies also attempted to identify early markers of functional engagement which would offer information on how VU319 may enhance cognition in patient sample in future studies. Method: A double‐blind Phase 1 human SAD study consisted of five cohorts of eight participants, in which six participants received oral VU319 and two participants received placebo. The Food Effect substudy consisted of 12 participants, in which ten received oral VU319 and two received placebo. The five doses for the SAD study were 60, 120, 240, 400 and 600mg. Participants in the Food Effect substudy received VU319 at a single dose of 120mg after a meal. All six cohorts combined typical safety and PK assessment with behavioral and brain‐based measures that targeted cognitive processes and was sensitive to cholinergic drug effects both at pre‐dose and again at 5‐7 hours post‐dose. Result: Results of the SAD and Food Effect studies have shown tolerability with no observed dose limiting side effects and no observed significant adverse events suggesting non‐M1 mAChR stimulation throughout the full dose range of the first five cohorts. PK evaluation showed good oral absorption and bioavailability with a half‐life consistent with once daily dosing. Absorption of VU319 was increased in a fed compared to a fasted state. Cognitive and electrophysiological results suggested functional target engagement of the task at higher fasting doses of VU319. Conclusion: Single dose VU319 across five ascending cohorts appeared to have a favorable safety profile and a PK profile consistent with once daily dosing. Administration of VU319 with food increased absorption and was associated with improvements in performance measures. These results provide a strong foundation for the planned multiple ascending dose study and a Phase 2a POC study in MCI.